Determinants and Sustainability of Remittances in Bangladesh: Do Skilled or Unskilled Labor Migrants Matter? - Faruq, Md. Omor (Finance & Economics Review, 2025)
Purpose: Remittances from overseas workers constitute a significant contribution to Bangladesh’s foreign exchange earnings. This study aims to investigate the primary determinants of remittance, with a focus on the skill composition of labor migrants and the sustainability of remittance inflows in Bangladesh. Methods: This paper employed the ARDL Bound testing approach for estimation because of several advantages. To verify the consistency of the ARDL method’s results, this study also employed the Dynamic OLS and Fully Modified OLS methods. This study used annual time series data from 1976 to 2021. Data are collected from the Bureau of Manpower Employment and Training, World Development Indicators, and International Financial Statistics. Results: This paper found that unskilled labor migrants are a significant determinant of remittance inflows in Bangladesh. This is a new finding, differing from previous empirical findings for Bangladesh. Moreover, a domestic country’s GDP, petroleum price, and exchange rate also significantly influence the inflows of remittances in Bangladesh. Besides, it was found that inflows of remittances followed an upward trajectory, with a sharp increase since 2001 and sustained over the period. By employing the ARIMA (12,1,11) forecasting model using monthly data, it is also found that, given the current policies and existing migration trends, remittance flows are expected to increase in the years to come. Implications: The findings of this study suggest that the inflow of remittances can be influenced by implementing proper policies in Bangladesh. As unskilled labor migrants are one of the significant determinants of remittances inflow in Bangladesh, it is necessary to explore new countries, except the GCC, based on those countries’ needs and willingness to hire migrant workers from Bangladesh. Moreover, allowing the depreciation of exchange rates consistent with economic fundamentals will increase the inflow of remittances in Bangladesh. Originality: This paper focuses on skill composition of labor migrants as a determinant of remittance inflows and analyzes the sustainability and near-term outlook of remittance inflows in Bangladesh. Limitations: This paper utilizes annual data from 1976 to 2021 and can’t expand the sample period beyond 2021 due to the unavailability of GDP data for certain GCC countries.